Microfoundations of Routines and Capabilities: Individuals, Processes, and Structure - Felin, Teppo; Foss, Nicolai J.; Heimeriks, Koen H.; Madsen, Tammy L. (Journal of Management Studies, 2012)
abstractThis article introduces the Special Issue and discusses the microfoundations of routines and capabilities, including why a microfoundations view is needed and how it may inform work on organizational and competitive heterogeneity. Building on extant research, we identify three primary categories of micro‐level components underlying routines and capabilities: individuals, social processes, and structure. We discuss how these components, and their interactions, may affect routines and capabilities. In doing so, we outline a research agenda for advancing the field's understanding of the microfoundations of routines and capabilities.